Unpacking constructs used to describe teachers’ mathematics knowledge for teaching: insights into MKT and MMT - Rocha, Abby (Frontiers in Education, 2025)
Over the past 30 years, researchers in the United States have investigated teachers’ mathematical knowledge and its interaction with their instructional practices. This research has produced a significant body of literature related to teachers’ Mathematical Knowledge for Teaching (MKT). A review of this body of literature revealed diversity in the ontological perspectives and research priorities, highlighting constructs such as MKT, Mathematical Meanings for Teaching (MMT), and Key Pedagogical Understandings (KPUs). This analysis provides a comprehensive overview of these constructs, detailing their definitions, applications, and interrelationships. By clarifying these concepts, the report aims to consolidate understanding and inform future research and practice in mathematics education.